Perlindungan Hukum bagi Whistleblower dalam Tindak Pidana Korupsi di Indonesia - Subhan Amin; Satria Unggul Prakasa Wicaksana (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
This study examines the Legal Protection for Whistleblowers in Corruption Crimes in Indonesia. The role of the reporter is very necessary or significant in law enforcement; with the presence of a whistleblower, law enforcers will be helped and more accessible in uncovering a case of a criminal act of corruption. Therefore, the state should provide legal protection to the complainants to protect their rights by law. Then the state should also give awards to the whistleblowers because this award is a form of appreciation from the state to the complainants for helping law enforcers and taking part in protecting the country. As in the case of a corruption reporter who was made a suspect in Cirebon, he should be legally protected from any charges. Still, he was made a suspect, so LPSK should assist as much as possible so that his rights are protected or given in full. Sothis study will answer several questions (1) Legal protection for Whistleblowers in corruption cases in Indonesia. (2) The legal mechanism within the framework of the criminal law system in ensuring security for Whistleblowers in corruption crimes. This study uses a socio-legal method that examines with the help of social science. First, the results showed legal protection for whistleblowers, namely in Article 10 of Law Number 31 of 2014 concerning protecting witnesses and victims, obtaining legal protection physically and psychologically and materially and non-materially. Second, the regulation of whistleblowers is still not explicitly regulated, so there is a need for special rules so that whistleblowers can be protected from threats and legal guarantees for whistleblowers.